Personality Factors in Colorectal Cancer: A Systematic Review - Galli, Federica; Scotto, Ludovica; Ravenda, Simona; Zampino, Maria Giulia; Pravettoni, Gabriella; Mazzocco, Ketti (Frontiers in Psychology, 2021)
Background: The role of personality in cancer onset and development has been studied for a long time. Since colorectal cancer (CRC) is one of the most prevalent cancer types and linked to lifestyle habits, it is important to better understand its psychological correlates, in order to design a more specific prevention and intervention plan. The aim of this systematic review is to analyze all the studies investigating the role of personality in CRC onset. Methods: All studies on CRC and personality up to November 2020 were scrutinized according to the Cochrane Collaboration and the PRISMA statements. Selected studies were additionally evaluated for the Risk of Bias according to the Newcastle-Ottawa Scale (NOS). Results: Eight studies met the inclusion criteria and were eventually included in this review. Two main constructs have been identified as potential contributors of CRC onset: emotional regulation and relational style. The third component, neuroticism, investigated in three studies, demonstrated no association with CRC onset. Conclusion: Strong conclusions regarding the influence of personality traits on the onset of CRC are not possible, because of the small number and the heterogeneity of the selected studies. Further research is needed to understand the complexity of personality and its role in the onset of CRC and the interaction with other valuable risk factors.